THE ROLE OF MEDICAL TOURISM IN ATTRACTING FOREIGNERS - Eshonkulova Shakhnoza Abdujabbor kizi (TADQIQOTLAR, 2025)
Abstract: the article discusses the key factors that allow Uzbekistan to take a strong position in the international market of medical services, competing in the world community.  The  global  trends  in  the  development  of  tourism  services  and  the possibilities  of  Uzbekistan  to  integrate  into  upward  trends  are  being  studied.  The advantages of the natural potential of the country, the success of the medical industry in  the  implementation  of  state  programs  to  attract  medical  tourists  and  encourage foreign investment are analyzed. The importance of using the experience of countries with developed medical tourism is emphasized.